Two Years of tranSMART in a University Hospital for Translational Research and Education - Christoph, Jan; Knell, Christian; Naschberger, Elisabeth; Stürzl, Michael; Maier, Christian; Prokosch, Hans-Ulrich; Sedlmayr, Martin (Studies in health technology and informatics, 2017)
For translational research, software platforms such as tranSMART with an integrated view of both clinical and omics data have gained more and more attention in the last years.We wanted to examine the success and failures of tranSMART in the fields of translational research and education by looking at the examples of six use cases at our hospital. We wanted to point out suitable scenarios and user groups as well as still existing challenges and limitations.We sum up the experience we made with our use cases with a focus on lessons learned.tranSMART was successfully established by a bottom-up approach at our university hospital and has been running for more than two years now. It has been used in four translational research projects as well as in education in the context of lectures and bachelor/master theses.tranSMART can be a very useful tool for translational research and education. But it should be used with both care and statistical knowledge to avoid wrong conclusions. Some technical constraints, especially for data modeling, still limit many applications. Version control and data provenance are remaining challenges.
EVALuna2:187